Biochemical characterization and cytotoxic effect of the skin secretion from the red-spotted Argentina frog Argenteohyla siemersi (Anura: Hylidae) - Fusco, Luciano Sebastian (2020)
Background: Argenteohyla siemersi (red-spotted Argentina frog) is a casque-headed tree frog species belonging to the Hylidae family. This species has a complex combination of anti-predator defense mechanisms that include a highly lethal skin secretion. However, biochemical composition and biological effects of this secretion have not yet been studied. Methods: The A. siemersi skin secretion samples were analyzed by mass spectrometry and chromatographic analysis (MALDI-TOF/MS, RP-HPLC and GC-MS). Proteins were also studied by SDS-PAGE. Among the biological activities evaluated, several enzymatic activities (hemolytic, phospholipase A2 , clotting, proteolytic and amidolytic) were assessed. Furthermore, the cytotoxic activity (cytolysis and fluorescence staining) was evaluated on myoblasts of the C2C12 cell line. Results: The MALDI-TOF/MS analysis identified polypeptides and proteins in the aqueous solution of A. siemersi skin secretion. SDS-PAGE revealed the presence of proteins with molecular masses from 15 to 55 kDa. Steroids, but no alkaloids or peptides (less than 5 kDa), were detected using mass spectrometry. Skin secretion revealed the presence of lipids in methanolic extract, as analyzed by CG-MS. This secretion showed hemolytic and phospholipase A2 activities, but was devoid of amidolytic, proteolytic or clotting activities. Moreover, dose-dependent cytotoxicity in cultured C2C12 myoblasts of the skin secretion was demonstrated. Morphological analysis, quantification of lactate dehydrogenase release and fluorescence staining indicated that the cell death triggered by this secretion involved necrosis. Conclusions: Results presented herein evidence the biochemical composition and biological effects of A. siemersi skin secretion and contribute to the knowledge on the defense mechanisms of casque-headed frogs.